2004
DOI: 10.1007/s00223-004-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Proportion of Organic Material in Bone on Thermal Decomposition of Bone Mineral: An Investigation of a Variety of Bones from Different Species Using Thermogravimetric Analysis coupled to Mass Spectrometry, High-Temperature X-ray Diffraction, and Fourier Transform Infrared Spectroscopy

Abstract: Thermogravimetric analysis linked to mass spectrometry (TGA-MS) shows changes in mass and identifies gases evolved when a material is heated. Heating to 600 degrees C enabled samples of bone to be classified as having a high (cod clythrum, deer antler, and whale periotic fin bone) or a low (porpoise ear bone, whale tympanic bulla, and whale ear bone) proportion of organic material. At higher temperatures, the mineral phase of the bone decomposed. High temperature X-ray diffraction (HTXRD) showed that the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 35 publications
9
119
0
Order By: Relevance
“…Even though bones possess various sizes and shapes, they share general chemical and structural features that, despite a static appearance on adult vertebrates, vary with and within species (Gamsjaeger et al, 2010;Mkukuma et al, 2004). In fact, among similar individuals, bone properties change with age, nutrition, hormonal equilibrium and health condition, in addition to other factors such as biomechanical environment (Aerssens et al, 1997;Fratzl et al, 2004).…”
Section: Bone Composition and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Even though bones possess various sizes and shapes, they share general chemical and structural features that, despite a static appearance on adult vertebrates, vary with and within species (Gamsjaeger et al, 2010;Mkukuma et al, 2004). In fact, among similar individuals, bone properties change with age, nutrition, hormonal equilibrium and health condition, in addition to other factors such as biomechanical environment (Aerssens et al, 1997;Fratzl et al, 2004).…”
Section: Bone Composition and Structurementioning
confidence: 99%
“…Although there is some controversy regarding the onset of chemical and structural changes as a consequence of heat treatment, it has been reported that changes in the mineral phase of bone are not significant until degradation and combustion of most of the more labile organic components occurs (around 500 ºC) (Etok et al, 2007;Mkukuma et al, 2004;Murugan et al, 2006;Ooi et al, 2007). Regarding sample mineralogy, it is generally accepted that heat treatment promotes the crystallinity of bone derived hydroxyapatite and increases the crystallite size (Etok et al, 2007;Hillera et al, 2003;Ooi et al, 2007).…”
Section: Bone-derived Hydoxyapatite: Influence Of the Calcination Temmentioning
confidence: 99%
“…Microscopically, the mineral phase, which accounts for 60-70 weight % [12] can be referred to as an impure, non-stoichiometric and poorly crystalline form of hydroxylapatite (HA), with a basic nanosized bioapatite structure of Ca10(PO4)6(OH)2 embedded in an organic matrix. This mineral phase may identify with dahllite, similar to hydroxyapatite but containing up to 7 wt % of carbonate [13][14][15][16][17]12].…”
Section: Introductionmentioning
confidence: 99%
“…3, Table 2). As bone mineral is considered to resemble an impure and poorly crystalline form of hydroxyapatite (HAP), with unit cell contents Ca 10 (PO 4 ) 6 (OH) 2 (Mkukuma et al, 2004), these XRD spectra suggest that the inlay material is for the most part mammal bone. Recent studies of the progressive heating of human bone show that the XRD trace shows a marked decrease in band widths between 400 and 600 C (Rogers and Daniels, 2002).…”
Section: Xrd Analysismentioning
confidence: 99%